2019
DOI: 10.1074/jbc.ra118.005761
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β (TGFβ) cross-talk with the unfolded protein response is critical for hepatic stellate cell activation

Abstract: Edited by Eric R. FearonTransforming growth factor ␤ (TGF␤) potently activates hepatic stellate cells (HSCs), which promotes production and secretion of extracellular matrix (ECM) proteins and hepatic fibrogenesis. Increased ECM synthesis and secretion in response to TGF␤ is associated with endoplasmic reticulum (ER) stress and the unfolded protein response (UPR). TGF␤ and UPR signaling pathways are tightly intertwined during HSC activation, but the regulatory mechanism that connects these two pathways is poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…The unfolded protein response (UPR) branch involved in fibrosis activation is protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK), which indirectly induces SMAD2. In TGFβ-treated HSCs induction of another UPR branch, IRE1α occurs [169]. In line with this, treatment of cells with hydrogen peroxide or ethanol feeding in vivo led to UPR activation, while abrogation of the IRE1α branch of the UPR inhibited HSC activation and autophagy [170].…”
Section: Er Stressmentioning
confidence: 65%
“…The unfolded protein response (UPR) branch involved in fibrosis activation is protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK), which indirectly induces SMAD2. In TGFβ-treated HSCs induction of another UPR branch, IRE1α occurs [169]. In line with this, treatment of cells with hydrogen peroxide or ethanol feeding in vivo led to UPR activation, while abrogation of the IRE1α branch of the UPR inhibited HSC activation and autophagy [170].…”
Section: Er Stressmentioning
confidence: 65%
“…Srebp 1c contributes to Hamp expression [81]. Activation of stellate cells is also integrated with Srebp regulation [82,83]. Srebp regulation may in some way connection to Cyp1b1 and retinol.…”
Section: Cyp1b1 and Dietary Retinol Selectively Support Postnatal Incmentioning
confidence: 99%
“…These same genes are substantially affected by a retinol-depleted maternal diet (GVAD) that lowers liver retinol. At birth, GVAD and Cyp1b1 deletion each suppress the iron regulator, Hamp, while also increasing multiple stellate activation markers, each a likely target of Srebp control [82,83]. The low presence of Lrat and retinyl esters and enrichment of activated stellate markers suggests an altered basal state that may be more sensitive to these changes [14].…”
Section: Conclusion and Key Questionsmentioning
confidence: 99%
“…Some of the GO terms that were identified in this study are not associated with any reported roles of the DAF-7 pathway, such as Response to Topologically Incorrect Protein. However, TGFβ has been reported to interact with the unfolded protein response in other model systems, such as hepatic stellate cells and corneal endothelial cells, suggesting this function is evolutionarily conserved [41,42]. Regardless of the novelty of the identified GO terms, the DEGs generated from these datasets provide specific gene targets that can be further studied to provide insight into the multifunctional TGFβ pathway.…”
Section: Discussionmentioning
confidence: 99%